High-frequency fluorescence monitoring in karst aquifers: A multivariate approach for early detection of anthropogenic contamination of water resources - Lucile Justy; Vincent Bailly-Comte; Pascal Brunet; Christelle Batiot-Guilhe (Science of The Total Environment, 2026)

Modelling light-sharing in agrivoltaics: the open-source Python Agrivoltaic Simulation Environment (PASE 1.0) - Roxane Bruhwyler; Nicolas De Cock; Pascal Brunet; Jonathan Leloux; Pierre Souquet; Etienne Perez; Etienne Drahi; Sebastian Dittmann; Frédéric Lebeau (Agroforestry Systems, 2024)

Influence of karst conduit’s geometry and morphology on 3D flow and transport processes: Insights from 3D tracer tests and numerical modelling - Mohammed Aliouache; Pierre Fischer; Pascal Brunet; Lionel Lapierre; Benoit Ropars; Frank Vasseur; Hervé Jourde (Journal of Hydrology, 2024)

Directional turnover towards larger‐ranged plants over time and across habitats - Ingmar R. Staude; Henrique M. Pereira; Gergana N. Daskalova; Markus Bernhardt‐Römermann; Martin Diekmann; Harald Pauli; Hans Van Calster; Mark Vellend; Anne D. Bjorkman; Jörg Brunet; Pieter De Frenne; Radim Hédl; et al. (Ecology Letters, 2022)
Species turnover is ubiquitous. However, it remains unknown whether certain types of species are consistently gained or lost across different habitats. Here, we analysed the trajectories of 1827 plant species over time intervals of up to 78 years at 141 sites across mountain summits, forests, and lowland grasslands in Europe. We found, albeit with relatively small effect sizes, displacements of smaller‐ by larger‐ranged species across habitats. Communities shifted in parallel towards more nutrient‐demanding species, with species from nutrient‐rich habitats having larger ranges. Because these species are typically strong competitors, declines of smaller‐ranged species could reflect not only abiotic drivers of global change, but also biotic pressure from increased competition. The ubiquitous component of turnover based on species range size we found here may partially reconcile findings of no net loss in local diversity with global species loss, and link community‐scale turnover to macroecological processes such as biotic homogenisation.

Disjunct populations of E uropean vascular plant species keep the same climatic niches - Safaa Wasof; Jonathan Lenoir; Per Arild Aarrestad; Inger Greve Alsos; W. Scott Armbruster; Gunnar Austrheim; Vegar Bakkestuen; H. John B. Birks; Kari Anne Bråthen; Olivier Broennimann; Jörg Brunet; Hans Henrik Bruun; et al. (Global Ecology and Biogeography, 2015)
Aim Previous research on how climatic niches vary across species ranges has focused on a limited number of species, mostly invasive, and has not, to date, been very conclusive. Here we assess the degree of niche conservatism between distant populations of native alpine plant species that have been separated for thousands of years. Location European A lps and F ennoscandia. Methods Of the studied pool of 888 terrestrial vascular plant species occurring in both the A lps and F ennoscandia, we used two complementary approaches to test and quantify climatic‐niche shifts for 31 species having strictly disjunct populations and 358 species having either a contiguous or a patchy distribution with distant populations. First, we used species distribution modelling to test for a region effect on each species' climatic niche. Second, we quantified niche overlap and shifts in niche width (i.e. ecological amplitude) and position (i.e. ecological optimum) within a bi‐dimensional climatic space. Results Only one species (3%) of the 31 species with strictly disjunct populations and 58 species (16%) of the 358 species with distant populations showed a region effect on their climatic niche. Niche overlap was higher for species with strictly disjunct populations than for species with distant populations and highest for arctic–alpine species. Climatic niches were, on average, wider and located towards warmer and wetter conditions in the Alps. Main conclusion Climatic niches seem to be generally conserved between populations that are separated between the A lps and F ennoscandia and have probably been so for 10,000–15,000 years. Therefore, the basic assumption of species distribution models that a species' climatic niche is constant in space and time – at least on time scales 10 4 years or less – seems to be largely valid for arctic–alpine plants.

Different effects of earthworms and ants on soil properties of paddy fields in North-East Thailand - Pascal Jouquet; Christian Hartmann; Chutinan Choosai; Yupa Hanboonsong; Didier Brunet; Jean-Pierre Montoroi (Paddy and Water Environment, 2008)

Is soil quality improvement by legume cover crops a function of the initial soil chemical characteristics? - Armand W. Koné; Jérôme E. Tondoh; Pascal K. T. Angui; France Bernhard-Reversat; Gladys Loranger-Merciris; Didier Brunet; Soumaïla T. K. Brédoumi (Nutrient Cycling in Agroecosystems, 2008)

Expressed sequence tags from the phytopathogenic fungus Botrytis cinerea - Muriel Viaud; Fabrice Legeai; Jean-Marc Pradier; Yves Brygoo; Frdrique Bitton; Jean Weissenbach; Adeline Brunet-Simon; Aymeric Duclert; Sabine Fillinger; Dominique Fortini; Anastasia Gioti; Corinne Giraud; et al. (European Journal of Plant Pathology, 2005)